2014
DOI: 10.1097/cmr.0000000000000097
|View full text |Cite
|
Sign up to set email alerts
|

Economic burden of brain metastases among patients with metastatic melanoma in a USA managed care population

Abstract: Malignant melanoma patients frequently relapse with metastases in the brain, making it the third most common cancer-causing brain metastases in the USA. Management of brain metastases remains challenging because of the rapid progression of disease and ineffectiveness of conventional therapies. This retrospective study, with a 'pre/post' design, quantifies the economic burden of brain metastases among melanoma patients in the USA. A large managed-care insurance claims database (2000 Q1-2011 Q3) was used to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Patients with distant recurrences had 186 more OP visits per 100 person-months in the year after recurrence compared with recurrence-free patients, whereas all-cause healthcare costs were higher by $14 953 PPPM in the year after recurrence. Previous studies in real-world USA populations have reported a range of $6773–62 859 PPPM for patients with metastatic melanoma 16 , 20 , 21 , 44 . Outside of the USA, including in developing countries, the cost per patient with melanoma was reported to range between $9162 and $86 875 14 , 45 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Patients with distant recurrences had 186 more OP visits per 100 person-months in the year after recurrence compared with recurrence-free patients, whereas all-cause healthcare costs were higher by $14 953 PPPM in the year after recurrence. Previous studies in real-world USA populations have reported a range of $6773–62 859 PPPM for patients with metastatic melanoma 16 , 20 , 21 , 44 . Outside of the USA, including in developing countries, the cost per patient with melanoma was reported to range between $9162 and $86 875 14 , 45 47 .…”
Section: Discussionmentioning
confidence: 99%
“…35 CNS involvement adversely impacts patient quality of life and is associated with increased costs and higher levels of health care resource utilization (HCRU). 1,4,36 Real-world studies estimating the cost of care can help inform treatment decisions for payers and clinicians. However, previous cost-estimate studies in patients with melanoma and CNS metastases were conducted before widespread use of targeted therapies and immunotherapies.…”
Section: What This Study Addsmentioning
confidence: 99%
“…However, previous cost-estimate studies in patients with melanoma and CNS metastases were conducted before widespread use of targeted therapies and immunotherapies. 36 Therefore, we conducted a real-world study to estimate costs and HCRU in patients with metastatic melanoma with and without CNS metastases in the current treatment era following introduction of targeted therapies (BRAF and MEK inhibitors) and immunotherapies (immune checkpoint inhibitors).…”
Section: What This Study Addsmentioning
confidence: 99%
“…The years of life lost to disease and the associated economic burden associated with brain metastases in melanoma is significant and underscores the need for more effective treatments to improve outcome in these patients. (3) Treatment options include surgery, whole brain radiotherapy (WBRT), stereotactic radiosurgery (SRS) and systemic therapy. Performance status, neurologic symptoms, extent of extracranial disease, along with size, number and location of brain metastases impact the management of brain disease.…”
Section: The Overall Treatment Paradigm For Melanoma Brain Metastasesmentioning
confidence: 99%